Impact of Johne's disease on a large-scale dairy farm a case study using cash flow analysis - Nguyen Tri Khiem (Asian Journal of Agriculture and Development, 2012)
The spread of animal diseases could cause long-lasting damage. The outbreak of infections is a destabilizing factor in the normal cash flow of dairy farms. The work and cost of disinfection can be considerable, depending on the scale of production, and lead to losses. The owner may have to pay for wages, feed and operation, even if production stops. Research data on the change in performance after the infection of Johne's disease for farmers is limited. Effective information is essential to dairy farmers on what kinds of disinfection measures are effective after outbreak. The farm in this study is a dairy farm in Hokkaido, Japan. It has as of 2010 about 300 cows and 50 hectares of grass land. Three family members and some hired workers were engaged in dairy farming. The first cow infected with Johne's diseases was confirmed in 1999 and more than 200 cows were culled for disinfection. The accounting data showed the change in the performance of this farm were used in the study. Results show that the depreciation cost of cows made from increased culling of infected animals creates a surplus of cash flow from operations. However, there was a decline in compulsive and/or voluntarily culled cows, and therefore a decline in sales of cows reduces cash flows from operation and free cash flow. Outbreaks of Johne's disease seriously impact the cash flow of large-scale dairy farms.